New technologies in education. The case of Spain - Luis Alberiko Gil-Alana; Silvia Alvarez-Santas (Cogent Education)
The use of active learning methodologies in higher education is a priority objective within the European Higher Education Area. The paradigm shift towards education in competences requires new teaching strategies focused on giving greater protagonism to students, putting them at the centre of their own learning process. In this transition, information and communication technologies (ICT) are playing a fundamental role. Virtual teaching has specific characteristics that make it possible to tailor the teaching-learning process in ways that are impossible by other means. Self-learning or ‘learning to learn’, promoted by the new paradigm of education in competences, is inseparable from the use of virtual learning tools. An analysis of data on the growth and prevalence of e-learning in Spain is conducted in the paper, and using new methodologies based on fractional integration we offer important insights into the growth of e-learning in volume and importance with respect to traditional teaching methodologies. This growing relevance has important implications for educators, educational institutions and governments that will have to adapt to the needs of a growing public that demands this type of training.